OVERVIEW OF TEXT RETRIEVAL ALGORITHMS - Shkurat, Oksana (Collection of scientific papers «ΛΌГOΣ», 2022)
Phonetic algorithms are effective tools using in text retrieval systems. Phonetic algorithms are used: